Expansion of the aphid Myzocallis (Lineomyzocallis) walshii (Monell) on the red oak Quercus rubra, and adaptation of local parasitoids in the northeastern Iberian Peninsula (Hom., Aphididae, Calaphidinae; Hym., Braconidae, Aphidiinae) - Pons, X; Lumbierres, B; Starý, P (Journal of Pest Science, 2005)
An ongoing expansion of Myzocallis (L.) walshii (Monell) in the NE Iberian Peninsula was detected. The aphid species was recorded in Catalonia, Andorra and Navarra. Adaptation of local native parasitoids (at least Trioxys pallidus Haliday and T. tenuicaudus Stary´) to the new immigrant was documented, together with background information on their host range in the native environments. The detection of parasitoids of M. walshii is the ﬁrst published evidence in Europe. The new evidence for M. walshii in the NE Iberian Peninsula also supports the warning of the expansion of the aphid as a pest of Quercus rubra over Europe.
Keywords: Aphids; Myzocallis walshii; Parasitoids; Quercus sp.; Trioxys pallidus; Trioxys tenuicaudus

Expansion of the aphid Myzocallis (Lineomyzocallis) walshii (Monell) on the red oak Quercus rubra, and adaptation of local parasitoids in the northeastern Iberian Peninsula (Hom., Aphididae, Calaphidinae; Hym., Braconidae, Aphidiinae) - Pons, X.; Lumbierres, B.; Starý, P. (Journal of Pest Science, 2005)
An ongoing expansion of Myzocallis (L.) walshii (Monell) in the NE Iberian Peninsula was detected. The aphid species was recorded in Catalonia, Andorra and Navarra. Adaptation of local native parasitoids (at least Trioxys pallidus Haliday and T. tenuicaudus Stary´) to the new immigrant was documented, together with background information on their host range in the native environments. The detection of parasitoids of M. walshii is the ﬁrst published evidence in Europe. The new evidence for M. walshii in the NE Iberian Peninsula also supports the warning of the expansion of the aphid as a pest of Quercus rubra over Europe.
Keywords: Aphids; Myzocallis walshii; Parasitoids; Quercus sp.; Trioxys pallidus; Trioxys tenuicaudus

Hymenoptera reared from Plagiotrochus suberi (Hymenoptera: Cynipidae) galls in California - Zuparko, R L (Pan-Pacific Entomologist, 1996)
Nine species of Hymenoptera were reared from stem galls induced by Plagiotrochus suberi Weld on Quercus suber L. in Albany, California. The most numerous species reared was P. suberi, but Euderus crawfordi Peck was the most common parasitoid reared. Other species reared were: Aprostocetus pattersonae (Fullaway), A. sp. nr. verrucarii (Balduf), Acaenacis taciti (Girault), Sycophila wiltzae(Balduf), Sycophila sp, possibly foliatae (Ashmead), Brasema sp. and Ceraphron sp. The rearings of all parasitoids (except E. crawfordi and S. wiltzae) constitute new host records. All described parasitoid species are native to North America and represent new associations with the introduced P. suberi.
Keywords: associations; Euderus crawfordi; Insecta; new; Parasitoids; Plagiotrochus suberi; Pragas e doenças do sobreiro - Plagiotrochus suber; Quercus suber